THE CONVERTIBLE MECHANISM OF THE CAR ROOF - Daniela ANTONESCU; Margareta STRÂMBEANU; Ovidiu ANTONESCU (Fiabilitate şi Durabilitate, 2021)
The paper deals with linkages used to actuate the retractable top of convertible passenger car, which are either a simple articulated 4-bar mechanism or a stacking multi-contour n-bar mechanism. The car top that can fold or unfold is consisting of two or three hard components. The folding linkage of the hard top is a planar kinematic chain with articulated bars which allows the two or three top parts to be stacked into the trunk room. To be observed that the first hard component of the kinematic chain is the car rear screen and the second hard part is actually the retractable top. In order to fold the car top and the rear screen, the door trunk is actuated by means of a simple hinge pair or a 4-bar mechanism. In the case of a larger passenger car, the top consists of two parts and together with the rear screen form the open kinematic chain which can be closed by means of some stacked kinematic chains. Using CAD modeling and kinematic simulation of the retractable textile car top linkage used on convertibles, the mechanism efficiency regarding its operation can be improved. Through Inventor® software the user can modify any part or subassembly of the mechanism at any moment. This can be done by means of the parametric design which allows that any changing on a component to be instantaneous reflected on the assembly which that part belongs to.